PENGEMBANGAN METODE RAPID VISUAL SCREENING HYBRID UNTUK EVALUASI KERENTANAN SEISMIK GEDUNG SEKOLAH - Enjang Wahyudin; Eko Walujodjati (CRANE: Civil Engineering Research Journal, 2026)
Indonesia faces high seismic risks, with over 62% of school buildings located in zones with Peak Ground Acceleration (PGA) . Conventional Rapid Visual Screening (RVS) methods, such as FEMA P-154, often misclassify confined masonry structures, leading to high false-negative rates. This study develops a Hybrid RVS method that integrates visual heuristics with field-measured quantitative parameters through a systematic five-module approach (Modules A to E). A field survey was conducted using a stratified random sampling of 102 primary schools () in Garut Regency. Module D (gap-filling parameters) utilizing non-destructive testing revealed sub-standard concrete quality, averaging 15.54–17.87 MPa. The mathematical derivation linking Wall Density Index (WDI) to base shear capacity demonstrated a strong exponential correlation () with the Demand-Capacity Ratio (DCR). To scientifically validate the Module E final scoring, a Tier-3 Performance-Based Seismic Evaluation (PBSE) using Nonlinear Static (Pushover) Analysis was performed using an equivalent diagonal strut macro-model in ETABS. The pushover results confirmed the RVS Hybrid diagnosis: a high-risk sample failed the Collapse Prevention target due to an extreme soft-story mechanism, recording an inter-story drift of 2.45%H. The proposed methodology recommends a new rule of thumb for practitioners, establishing a minimum WDI threshold of 2.50% to ensure structural adequacy, thereby supporting prioritized seismic retrofitting and the issuance of Building Reliability Certificates (SLF).